Effect of pregnancy on female gait characteristics: a pilot study based on portable gait analyzer and induced acceleration analysis - Li, Xin; Lu, Zhenghui; Cen, Xuanzhen; Zhou, Yizheng; Xuan, Rongrong; Sun, Dong; Gu, Yaodong (Frontiers in Physiology, 2023)
The changes in physical shape and center of mass during pregnancy may increase the risk of falls. However, there were few studies on the effects of maternal muscles on gait characteristics and no studies have attempted to investigate changes in induced acceleration during pregnancy. Further research in this area may help to reveal the causes of gait changes in women during pregnancy and provide ideas for the design of footwear and clothing for pregnant women. Forty healthy participants (20 pregnant and 20 non-pregnant women) participated in this study. The portable gait analyzer was used to collect participants’ conventional gait parameters. The adjusted OpenSim personalized musculoskeletal model analyzed the participants’ kinematics, kinetics, and induced acceleration. Independent sample T-test and one-dimensional parameter statistical mapping analysis were used to compare the differences in gait characteristics between pregnant and non-pregnant women in the third trimester. Compared with the control group, the women’s walking speed, stride length, stride frequency, thigh acceleration, swing work, and leg falling strength in the third trimester of pregnancy were significantly decreased (p<0.01). Induced acceleration analysis showed that muscle-induced acceleration decreased in the third trimester of pregnancy (p<0.01). However, the contribution of gastrocnemius muscle to the hip joint and knee joint increased (p<0.01). Compared with non-pregnant women, the gait characteristics, movement amplitude, and joint moment of women in the third trimester of pregnancy changed significantly. In addition, the results of induced acceleration analysis showed that the effect of gastrocnemius muscle on hip flexion and knee joint extension increased. This change may be due to an adaptive change in body shape and mass during pregnancy.